Impact of traffic load and spectral occupancy on Gaussian noise models performance for multiband networks - Venda, P.; Rebola, J.; Cancela, L. (2022 13th International Symposium on Communication Systems, Networks and Digital Signal Processing (CSNDSP), 2022)
In a network scenario, wavelength division multiplexing channels are added and dropped leading to fluctuations on the network traffic loads along the optical path. In this work, a comparison between the optical signal-to-noise ratio (OSNR) predictions of the recently proposed closed-form generalized Gaussian noise (GGN) model and a closed-form Gaussian noise (GN) model that does not take into account the stimulated Raman scattering (SRS) is performed, for different network traffic loads and spectral occupancy over the entire C+L band. In all results obtained, the maximum difference between the OSNR predictions of GN (without SRS) and GGN models closed forms is below 0.7 dB at optimum OSNR and maximum C+L band occupancy, indicating that the GN-model can also be used in C+L band transmission. For channel launch powers higher than the optimum, the OSNR differences increase up to 3 dB, being the GN-model (without SRS) unsuitable to assess the network performance in such situations.